HUKUM MENGULANG SALAT JAMAAH DALAM SATU MASJID MENURUT EMPAT MAZHAB - Miftah Faridh; Afif Amrullah (Fakultas Syariah UIN Antasari, 2018)
Abstract: This study aims to determine the law and legal basis (istidlāl) of repeating congregational prayers in one mosque according to the opinions of four schools, namely the Hanafi, Maliki, Syafi'i, and Hanbali schools. This research is a normative descriptive analytical study with a comparative approach. The results showed: First, the Hanafi, Maliki, and Syafi'i schools argued that the law of repeating (ie establishing) congregational prayers after the first congregation is makruh. This is if the mosque already has an imam, muezzin, and regular congregation. Meanwhile, the Hanbali school is of the opinion that it is permissible in addition to the Grand Mosque and the Prophet's Mosque. Second, the arguments used by the Hanafi school, the Maliki school, and the Syafi'i school are: (1) the hadith of the Prophet. never been late to pray then he did not do it in congregation at the mosque, (2) the history of the friends praying individually if they missed the congregational prayer, (3) repeating the congregation is not an act of salaf, (4) causing division of the Muslims, and (5) opening up opportunities underestimating congregational prayers. Meanwhile, the arguments of the Hanbali school are: (1) the generality of the hadith about the virtue of congregational prayer, (2) the hadith of the Prophet. advising someone to accompany a friend who has not prayed in congregation, (3) there is an age that is not used as a habit, and (4) it is not an intention to separate himself from the Muslim congregation.Abstrak: Penelitian ini bertujuan untuk mengetahui hukum dan dasar hukum (istidlāl) mengulang pelaksanaan salat jamaah dalam satu masjid menurut pendapat empat mazhab, yakni mazhab Hanafi, maliki, Syafi’i, dan Hanbali. Penelitian ini merupakan penelitian normatif yang bersifat deskriptif analitis dengan pendekatan komparatif. Hasil penelitian menunjukkan: Pertama, mazhab Hanafi, Maliki, dan Syafi’i berpendapat bahwa hukum mengulang (yakni mendirikan) salat jamaah setelah jamaah pertama adalah makruh. Hal ini jika di masjid tersebut sudah memiliki imam, muazin, dan jamaah tetap. Sedangkan mazhab Hanbali berpendapat boleh selain di Masjidil Haram dan Masjid Nabawi. Kedua, argumentasi yang digunakan mazhab Hanafi, mazhab Maliki, dan mazhab Syafi’i adalah: (1) hadis Nabi Saw. pernah terlambat salat kemudian beliau tidak melakukannya berjamaah di masjid, (2) riwayat para sahabat salat sendiri-sendiri apabila ketinggalan salat jamaah, (3) mengulang jamaah bukan perbuatan salaf, (4) menimbulkan perpecahan kaum muslimin, dan (5) membuka peluang orang meremehkan salat berjamaah. Sedangkan argumentasi mazhab Hanbali adalah: (1) keumuman hadis tentang keutamaan salat berjamaah, (2) hadis Nabi Saw. menganjurkan seseorang untuk menemani sahabatnya yang belum salat berjamaah, (3) ada uzur yang tidak dijadikan kebiasaan, dan (4) bukan niat untuk memisahkan diri dari jamaah kaum muslimin.